Pengaruh Pelatihan Efikasi Diri terhadap Keterikatan Kerja Perawat Rumah Sakit Umum Daerah di Sulawesi Selatan - Dewi Tri Resky Yanti; Fuad Nashori; Faraz Faraz (JIP (Jurnal Intervensi Psikologi), 2018)
This study aims to determine the effect of self-efficacy training on  work engagement of nurses at regional general hospital in South Sulawesi. The hypothesis of this study is self-efficacy training can improving work engagement of nurses at regional general hospital in South Sulawesi. The subjects of this study were 12 nurses, 6 nurses for the experimental group and 6 nurses for the control group from four care rooms: interna (I and VII), child (II), and surgical (V) with civil service status the hospital is at least 1 year, minimum education D3 Nursing and has a level of work engagement included in the category of medium. This study used the scale of work engagement (UWES) adapted by Christian, Hastjarjo, Ancok, and Meiyanto (2013) and the self-efficacy scale compiled by Valentino and Himam (2013) using self-efficacy dimensions expressed by Bandura (1977,1986). This research is a quasi experimental research with non-randomized pretest-posttest control group design using Mann-Whitney and Friedman’s test analysis technique. The result of data analysis showes that the hypothesis was rejected.